O-7 Nationwide adoption of an ACP program by a large U.S. health provider (HMO). (1st September 2015) - Johnson, Daniel; Chen, C; Kumar, R; Stern, M; Schriener, P; Peacock, L; Scott, A
Abstract : Background: Kaiser Permanente (KP) is America's largest non-profit health plan and integrated healthcare delivery system serving nearly 10 million members across 8 states. Historically, KP has lacked a systematic approach to advance care planning (ACP). Aim: KP's Care Management Institute (CMI) serves to support identification and spread of national best practice. CMI is supporting widespread adoption of a proven, systematic approach to ACP across all KP regions. Methods: In late 2013, KP Northern California commenced implementation of an evidence-based approach to ACP. CMI has since supported interregional spread by negotiating national training contracts, educating and engaging cross-regional leadership, coordinating interregional sharing and metrics, and constructing a best-practice implementation guide. Results: Three of KP's seven regions (serving 85% of all membership) have initiated implementation of systematic ACP. A fourth will start in 2016. Regions not yet participating cite insufficient resources and staff, and competing priorities. As of 1/2015, the organisation has trained 850 facilitators who have completed nearly 14, 000 conversations. Early outcomes include high concordance between member wishes and care delivered. Discussion: CMI and regional ACP leaders identify five key success factors for adoption and spread: upfront investment in critical infrastructure; organisation-wide inspiration of top-to-bottom stakeholders; proactive team engagement and support; elimination of barriers and silos; and incorporation of continuous quality improvement. Conclusion: National adoption of an evidence-based, systematic ACP in a large integrated health system appears feasible. Speed of adoption and spread depend on organisational will to invest in critical infrastructure and a top-to-bottom, sustained commitment to change.